2022
DOI: 10.3390/children9010078
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Vitamin K2 (Menaquionones) in Children’s Health and Diseases: A Review of the Literature

Abstract: Vitamin K2 activates vitamin K-dependent proteins that support many biological functions, such as bone mineralization, the inhibition of vascular stiffness, the improvement of endothelial function, the maintenance of strong teeth, brain development, joint health, and optimal body weight. Due to the transformation of food habits in developed countries over the last five decades, vitamin K and, specifically, vitamin K2 intakes among parents and their offspring have decreased significantly, resulting in serious h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 92 publications
(85 reference statements)
0
18
0
Order By: Relevance
“…In children, obesity, lack of exposure to direct sunlight, and season (spring) have been reported as risk factors for vitamin D deficiency [ 5 ]; vitamin D deficiency is associated with increased risk and severity of fractures [ 6 ]. Vitamin K deficiency has also been found to be a risk factor for increased fractures in children, similar to vitamin D deficiency [ 7 ]. In addition, it has been suggested that vitamin D and K deficiencies not only increase fracture risk but also affect fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…In children, obesity, lack of exposure to direct sunlight, and season (spring) have been reported as risk factors for vitamin D deficiency [ 5 ]; vitamin D deficiency is associated with increased risk and severity of fractures [ 6 ]. Vitamin K deficiency has also been found to be a risk factor for increased fractures in children, similar to vitamin D deficiency [ 7 ]. In addition, it has been suggested that vitamin D and K deficiencies not only increase fracture risk but also affect fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin K2-related proteins alter bone mineralization, vascular health, brain development, and the ideal body weight. 7 Various epidemiological findings discovered that vitamin K2 might support cardiovascular health and inhibit vascular calcification. 25,26 This research was constructed to observe the impact of MK-4 on cardiac I/R injury in isolated heart preparation of adult male rats.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin K2 analog, menatetrenone, or menaquinone-4 (MK-4), is present in animal products and is typically synthesized by tissue and bacterial conversion of dietary plant vitamin K1. 6,7 It regulates bone metabolism and steroid transcription factors, inhibits vascular calcification, and prevents oxidative stress-induced cell death without glutathione. [8][9][10] In individuals with the calcific aortic valve, vitamin K2 treatment improved vascular calcification and slowed the course of aortic valve calcification.…”
Section: Introductionmentioning
confidence: 99%
“…The compounds produced by B. subtilis natto are contained in the finally produced natto. Therefore, it seems that the beneficial health functions of natto that have been reported in the past are largely due to the components produced by B. subtilis natto (Chan et al, 2021; Kozioł‐Kozakowska & Maresz, 2022; Wang, Gao, et al, 2020; Y. Yang et al, 2021; L. Yuan et al, 2022). On the other hand, several reports have focused on compounds contained not in B. subtilis natto but in natto as a whole.…”
Section: Functional Compounds Produced By B Subtilis Nattomentioning
confidence: 99%
“…Among these, natto, produced by fermentation of soybeans by “ Bacillus subtilis natto (a subspecies of Bacillus subtilis ),” has been consumed in Japan as a traditional fermented food for at least a thousand years (Akbulut et al, 2020). Natto is attracting interest as a potential functional food for health, and has been reported to exhibit antithrombotic, antihypertensive, antiosteoporotic, antidiabetic, antioxidant, antiobesity, LDL‐lowering, and cholesterol‐lowering activities (Chan et al, 2021; Kozioł‐Kozakowska & Maresz, 2022; P. Wang, Gao, et al, 2020; Y. Yang et al, 2021; L. Yuan et al, 2022). Recently, development of new products of natto for the human health function has been under consideration (Chakrabarti et al, 2018; Shimakage et al, 2012).…”
Section: Introductionmentioning
confidence: 99%